Multi-frequency sound production and mixing in graphene - M. S. Heath (Nature Portfolio, 2017)
Abstract The ability to generate, amplify, mix and modulate sound in one simple electronic device would open up a new world in acoustics. Here we show how to build such a device. It generates sound thermoacoustically by Joule heating in graphene. A rich sonic palette is created by controlling the composition and flow of the electric current through the graphene. This includes frequency mixing (heterodyning), which results exclusively from the Joule mechanism. It also includes shaping of the sound spectrum by a dc current and modulating its amplitude with a transistor gate. We show that particular sounds are indicators of nonlinearity and can be used to quantify nonlinear contributions to the conduction. From our work, we expect to see novel uses of acoustics in metrology, sensing and signal processing. Together with the optical qualities of graphene, its acoustic capabilities should inspire the development of the first combined audio-visual nanotechnologies.